2018
DOI: 10.1021/acsomega.8b00447
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal Growth of Hybrid Lead Bromide Perovskites Using a Spin-Coating Method

Abstract: Synthesis and studies of single crystals of hybrid perovskite are important for achieving a better understanding of the optoelectronic phenomena occurring in this material and for improving ongoing applications. Here, we report on the growth of micrometer-size single crystals of methylammonium lead bromide (MAPbBr 3 ) using the spin coating deposition method on a quartz substrate. We studied the influence of the rotation speed and the use of three different additives N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…This is quite surprising because self‐assembly during spin coating can produce single crystal growth on amorphous silicon oxide rather than single crystal substrates. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is quite surprising because self‐assembly during spin coating can produce single crystal growth on amorphous silicon oxide rather than single crystal substrates. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…This is quite surprising because self-assembly during spin coating can produce single crystal growth on amorphous silicon oxide rather than single crystal substrates. [46] Another combination of MeOH and AcN solvents is also investigated, where AcN has relatively lower polarity with the highest dielectric constant. The relative humidity during sample synthesis was about 28%.…”
Section: Binary Co-solvent Methodsmentioning
confidence: 99%
“…Garcia‐Aboal et al synthesized MAPbBr 3 2D single crystals of several micrometers in length by controlling the rotational speed of spin coating and adding different additives. [ 74 ] Gao et al also investigated the effect of adding different concentrations of benzophenone (BP) to precursors of perovskite. [ 75 ] Moreover, Abe et al prepared different types of perovskite single crystals with a size of 5–30 μm on a low hydrophilic surface (Figure 7b).…”
Section: Preparation Strategies For 2d Perovskite Single Crystalsmentioning
confidence: 99%
“…The unfavorable thickness of bulk perovskite single crystals and the difficulties in the preparation of large-area films limit the development of perovskite single-crystal optoelectronic devices [ 24 , 26 , 27 , 29 , 30 ]. In recent years, researchers have prepared perovskite films composed of single crystals by introducing organic molecules to regulate the growth of perovskite during the spin coating [ 7 , 31 , 32 , 33 , 34 ]. Gao et al [ 34 ] reported a high-quality MAPbBr 3 film consisting of micron-scale single crystals by introducing benzophenone as a crystallization agent.…”
Section: Introductionmentioning
confidence: 99%